2013
DOI: 10.1182/blood-2012-10-461442
|View full text |Cite
|
Sign up to set email alerts
|

Influence of KIR gene copy number on natural killer cell education

Abstract: Key Points KIR gene copy number variation influences NK cell education at the repertoire level due to a linear effect on KIR expression. No effect of KIR gene dose on NK cell education at the single cell level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 16 publications
7
72
2
Order By: Relevance
“…Even a single nucleotide mutation can dramatically change receptor expression,25, 31, 32, 33 ligand specificity34, 35, 36 or signalling strength. KIR gene copy number variation influences NK cell education, shaping the NK cell repertoire 37. Lastly, combinatorial diversity of KIR and HLA class I alleles also impacts NK cell function, because any given KIR allotype has differential reactivity to the allotypes of its cognate HLA class I ligand 38, 39, 40, 41, 42, 43.…”
Section: Kir Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even a single nucleotide mutation can dramatically change receptor expression,25, 31, 32, 33 ligand specificity34, 35, 36 or signalling strength. KIR gene copy number variation influences NK cell education, shaping the NK cell repertoire 37. Lastly, combinatorial diversity of KIR and HLA class I alleles also impacts NK cell function, because any given KIR allotype has differential reactivity to the allotypes of its cognate HLA class I ligand 38, 39, 40, 41, 42, 43.…”
Section: Kir Geneticsmentioning
confidence: 99%
“…KIR3DL1*004 null allele is present at a mean frequency of 24·2% (SD 10·3) in worldwide populations 56. The frequency of cells positive for a given KIR is tightly linked to KIR gene copy number; a donor with two copies of KIR3DL1 will have a greater frequency of KIR3DL1 + NK cells than donors with only one copy,37, 38, 142 suggesting that each KIR gene copy is regulated independently. Additionally, NK cell KIR expression is related to cellular differentiation.…”
Section: Kir Gene Expressionmentioning
confidence: 99%
“…During development, NK cells acquire a functional potential that is, in part, determined by the capacities of each NK cell to engage its inhibitory receptors with self HLA class I molecules (7). In addition, the number of KIR gene copies contributes to increased NK cell responsiveness (8). Different theories have been proposed to explain the formation of the KIR NK cell repertoire.…”
mentioning
confidence: 99%
“…4 Recently, Beziatz et al also showed a linear effect of KIR gene copy number variation and HLA ligands on the overall functional responsiveness of the NK cell repertoire by analyzing KIR-HLA genotypes of healthy human volunteers. 5 Despite the accumulating evidence suggesting a quantitative effect of NK cell licensing in basic studies, its clinical impact on neoplastic diseases has never been demonstrated. This year, we were the first to report the impact of multiplicity of functional KIR-HLA compound genotypes on HCC recurrence after curative hepatectomy.…”
mentioning
confidence: 99%
“…This result matches the previously postulated theory that the number and type of host MHC class I alleles quantitatively tune the responsiveness of individual NK cell subsets expressing the corresponding KIR. 5 Highly licensed patients may equip NK cells with more vigorous immune-surveillance activity to act as potent constitutive immune effectors against both intrahepatic metastasis and de novo carcinogenesis, as compared to poorly licensed patients (Fig. 1).…”
mentioning
confidence: 99%